EVALUASI SARANA DAN PRASARANA PARIWISATA PANTAI SELATAN DI DAERAH ISTIMEWA YOGYAKARTA (Studi Kasus: Pantai Parangtritis, Baron, dan Pulangsawal atau Indrayanti) - M. Shahab; Djoko Sulistyo; M. Fauzie Siswanto (Universitas Quality, 2022)
The south coast tourism of Java Island is a tourist destination in demand in the Special Region of Yogyakarta. This can be seen from tourist visits in the 2016-2020 period as many as 28 million visitors. In supporting the development of national tourism based on PP no. 50 of 2011, it is necessary to provide adequate south coast tourism facilities and infrastructure. This study aims to identify the availability and comparison of tourism facilities and infrastructure according to tourist ratings in the Parangtritis, Baron, and Pulangsawal or Indrayanti beaches. The research method used in this study is a quantitative descriptive method with a simple random sampling technique. Samples were taken from 99 respondents (visiting tourists), consisting of 108 indicators divided into 21 research variables in each of these coastal tourist destinations. Data were collected through observation, interviews, and distribution questionnaires. Data analysis using Likert Scale data analysis. The results of this study indicate that tourism facilities and infrastructure in the tourist areas of Parangtritis, Baron, and Pulangsawal or Indrayanti beaches, according to tourists, are generally included in the Good category. The analysis of the average assessment shows that Parangtritis and Baron Beach are tourist destinations that are included in the Good category with a score of 67.2% and 61.8%, while Indrayanti Beach is in the Fair category with a score of 60.6%.